2011
DOI: 10.1007/s11214-010-9740-1
|View full text |Cite
|
Sign up to set email alerts
|

The Diffusion Region in Collisionless Magnetic Reconnection

Abstract: A review of present understanding of the dissipation region in magnetic reconnection is presented. The review focuses on results of the thermal inertia-based dissipation mechanism but alternative mechanisms are mentioned as well. For the former process, • combination of analytical theory and numerical modeling is presented. Furthermore, • new relation between the electric field expressions for anti-parallel and guide field reconnection is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
122
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 144 publications
(139 citation statements)
references
References 46 publications
16
122
0
Order By: Relevance
“…Specifically, we now know that reconnection is typically fast, 1 even though the rate may vary depending on the presence of magnetic islands, 2 and reconnection appears to be mediated by thermal inertia effects, which most prominently manifest themselves in form on nongyrotropic behavior of charged particles of all types, including electrons. 3,4 We further understand that the reconnection electric field is self-consistently required to maintain both current density and plasma pressure in the diffusion region, 5 and that a substantial component of outflow energy is in form of enthalpy flux. 6,7 Strictly speaking, however, symmetric systems are an exception, even though they are often seen as a good approximation to the night side of Earth's magnetosphere.…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, we now know that reconnection is typically fast, 1 even though the rate may vary depending on the presence of magnetic islands, 2 and reconnection appears to be mediated by thermal inertia effects, which most prominently manifest themselves in form on nongyrotropic behavior of charged particles of all types, including electrons. 3,4 We further understand that the reconnection electric field is self-consistently required to maintain both current density and plasma pressure in the diffusion region, 5 and that a substantial component of outflow energy is in form of enthalpy flux. 6,7 Strictly speaking, however, symmetric systems are an exception, even though they are often seen as a good approximation to the night side of Earth's magnetosphere.…”
Section: Introductionmentioning
confidence: 98%
“…However, over longer timescales these simulations reveal a new scenario in which flux ropes can be generated through secondary instabilities in the highly extended electron-scale current sheets that form nonlinearly during the onset of reconnection. These electron layers are a general feature of fast reconnection in collisionless plasmas and play a crucial role in breaking the frozen-in condition [1][2][3][4] . In sufficiently large systems, previous 2D simulations have demonstrated that these layers may become highly extended and form secondary magnetic islands [5][6][7][8][9][10] .…”
mentioning
confidence: 99%
“…Below the electron inertial length scale, even electrons are no longer frozen-in along the magnetic field lines. The electron inertial term and anisotropic electron pressure term have important roles [18,[26][27][28][29][30][31]. The reconnection rate is dominated by the Hall effect because of the electron inertial length being smaller than the ion inertial length.…”
mentioning
confidence: 99%